Promoting the Quality and Accessibility of Higher Education for People with Disabilities in the Russian Federation - Margolis A. A.; Rubtsov V. V.; Serebryannikova O. A. (Moscow State University of Psychology and Education, 2017)
The paper focuses on the main aspects of working towards making quality higher education accessible for persons with disabilities. The paper reveals specific educational conditions necessary for teaching and supporting students with disabilities, such as: developing and implementing career guidance programmes, adapted educational programmes, programmes for social psychological support, programmes for employment assistance and post-graduate support of students. Adaptation of educational programmes implies not only establishing a set of common requirements for adjusting the educational process to teaching individuals with disabilities depending on the specifics of their disability, but it also implies developing universal approaches and requirements for providing special settings in which their learning takes place. It is important that physical (architectural), informational, academic services and facilities be available for students with different disabilities and that members of the staff of an education organization have special competencies for working with the disabled persons. The paper also stresses the necessity of developing and implementing an effective model of extending the successful experience that a number of universities have in teaching students with disabilities to the system of higher education in general. This major goal could be achieved through the establishment of a network of resource and training centers in the regions of Russia.